2015
DOI: 10.1519/jsc.0000000000000971
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Variable Resistance Training on Maximal Strength

Abstract: Variable resistance training (VRT) methods improve the rate of force development, coordination between antagonist and synergist muscles, the recruitment of motor units, and reduce the drop in force produced in the sticking region. However, the beneficial effects of long-term VRT on maximal strength both in athletes and untrained individuals have been much disputed. The purpose of this study was to compare in a meta-analysis the effects of a long-term (≥7 weeks) VRT program using chains or elastic bands and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 36 publications
1
55
0
3
Order By: Relevance
“…It often requires access to fitness center facilities, which can be expensive and imposes extra training sessions in addition to the specific handball sessions. Elastic resistance bands have been suggested as a good alternative to traditional strength training equipment 24 . Elastic resistance bands are inexpensive, easy to use, portable, and easier to implement in regular handball training sessions than conventional resistance training equipment.…”
Section: Introductionmentioning
confidence: 99%
“…It often requires access to fitness center facilities, which can be expensive and imposes extra training sessions in addition to the specific handball sessions. Elastic resistance bands have been suggested as a good alternative to traditional strength training equipment 24 . Elastic resistance bands are inexpensive, easy to use, portable, and easier to implement in regular handball training sessions than conventional resistance training equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Next, because body height is the primary factor in determining the displacement of resistance (Soria-Gila, et al, 2015), participants were recruited in order to establish normative values for displacement during the SQ exercise. These normative values were then used to develop equations for displacement as a function of body height for both men and women.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Previous findings suggest that combined training programs can produce significant increases in strength and power in mesocycle-length timeframe as part of a periodized program with athletes (Soria-Gila, et al, 2015). In order to better support integration of the combined rubber band plus free weight training, information must be available for tracking work and therefore total training stimulus during transitions between free weight only and combined mesocyles.…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baker and Newton (4) proposed that the addition of chains alters the kinetic profile of the strength exercise by allowing an increased duration of acceleration throughout the range of motion and an ability to maintain higher forces towards the end of the movement. A recent meta-analysis by Soria-Gila et al (31) reported greater strength gains in programmes using chains compared to conventional training, with significant increases observed in both trained and untrained populations where programmes lasted >7 weeks.…”
Section: Introductionmentioning
confidence: 99%